2011
DOI: 10.1186/1471-2164-12-s3-s6
|View full text |Cite
|
Sign up to set email alerts
|

ApicoAlign: an alignment and sequence search tool for apicomplexan proteins

Abstract: BackgroundOver the recent years, a number of genomes have been successfully sequenced and this was followed by genome annotation projects to help understand the biological capabilities of newly sequenced genomes. To improve the annotation of Plasmodium falciparum proteins, we earlier developed parasite specific matrices (PfSSM) and demonstrated their (Smat80 and PfFSmat60) better performance over standard matrices (BLOSUM and PAM). Here we extend that study to nine apicomplexan species other than P. falciparum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 18 publications
2
15
0
Order By: Relevance
“…In our earlier studies [9,10] and this study, we have demonstrated that SMAT80 gave better E-values and better bit scores for most of the apicomplexan proteins. Next, we were interested to know whether parasite specific matrices would give poor E-values and/or bit scores for the proteins for which orthologs must not exist (in biological context) in a particular family/class of Apicomplexa.…”
Section: Resultssupporting
confidence: 59%
See 4 more Smart Citations
“…In our earlier studies [9,10] and this study, we have demonstrated that SMAT80 gave better E-values and better bit scores for most of the apicomplexan proteins. Next, we were interested to know whether parasite specific matrices would give poor E-values and/or bit scores for the proteins for which orthologs must not exist (in biological context) in a particular family/class of Apicomplexa.…”
Section: Resultssupporting
confidence: 59%
“…However we have shown that the choice of matrices can also significantly improve the ortholog detection in our previous [9,10] and the present studies. SMAT80 uniquely detected orthologs for 16, 166, 11, 21, 32, 72, 31, 185, 717, 7, 3, 5, 291, 20 and 191 proteins of Babesia bovis, Theileria annulata, Theileria parva, P. berghei, P. chabaudi, P. falciparum, P. knowlesi, P. vivax, P. yoelii yoelii, Cryptosporidium hominis, Cryptosporidium muris, Cryptosporidium parvum, Eimeria tenella, Neospora caninum and Toxoplasma gondii respectively (Figure 4).…”
Section: Resultssupporting
confidence: 58%
See 3 more Smart Citations